2016
DOI: 10.22146/ipas.11254
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology of Eight Hybrid Oil Palms Under Iron (Fe) Toxicity

Abstract: The research aims to study the change of morphology root characters of eight hybrid oil palms under iron toxicity (Fe). Field experiment done in arranged in a Randomized Complete Block Design (RCBD) two factors and three blocks as replications. The first factor was Fe concentration. It consists of two levels which are concentration 0µ.g-1 and concentration 600 µg.g-1 Fe. The second factor is the hybrid of oil palms which consists of eight hybrid oil palms as Yangambi, Avros, Langkat, PPKS 239, Simalungun, PPKS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A reduced root surface area can be explained as a strategy to restrict nutrient absorption (Kirk et al, 2022). Nurmalasari et al (2016) observed a reduction in SA due to Fe toxicity in oil palm. The reduction in the SA may be considered as a potential mechanism for Fe exclusion, evidenced by a decrease in the number of root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced root surface area can be explained as a strategy to restrict nutrient absorption (Kirk et al, 2022). Nurmalasari et al (2016) observed a reduction in SA due to Fe toxicity in oil palm. The reduction in the SA may be considered as a potential mechanism for Fe exclusion, evidenced by a decrease in the number of root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…Optimum amount of Fe in soil will enhance the nutrients uptakes by the plant. However, elevated level of Fe will cause toxicity effect and restrict the oil palm development (Nurmalasari et al, 2016). Iron contamination has the ability to alter the plant's morphology, anatomy, and physiology.…”
Section: P R E S Smentioning
confidence: 99%
“…The redyellow podzolic characteristics are high acidity level, a predominance of acid reacting cations, and deficiency of alkaline reagent cations. The dominant acid reagent cations are aluminium (Al), iron (Fe), and manganese (Mn) (Alam et al 2020;Febriani et al 2017;Irawan and Putra 2019;Khoiriyah et al 2016;Nurmalasari et al 2016;Ratnasari et al 2017;Utami et al 2019).…”
Section: Introductionmentioning
confidence: 99%